Water Clover Extract in Liprotein Lipase enzyme Activity of The Rats with High Cholesterol Diet - Dewinta Hayudanti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
Hypertriglyceridemia or high blood triglyceride levels is one of the lipid fraction disorders associated with an increased risk of cardiovascular disease. Flavonoids has an important role as cardioprotection by lowering triglyceride levels. The flavonoids in water clover contain 10,71 mg of extract. This research aims to prove that flavonoids can increase Lipoprotein Lipase enzymes activity. True experimental study used design pre-post test control group design in rats. The sample was selected based on by completed randomized design sampling to be devided into five groups, the control positive (n=5) were only given normal diet, control negative (n=5) were only given high cholesterol diet and treatment groups with three doses (n=15) were given cholesterol diet during the 7 days and water clover extract that intervention during the 14 days. The results of this research can increase activity of Lipoprotein Lipase enzymes as an influence of water clover extract based on Paired T-Test, before and after treatment there was a significant different (p<0.05). Activity of Lipoprotein Lipase enzymes in the negative control group and third treatment showed a significant difference (p.< 0.05) based on MANOVA (Multivariate Analyses of Variance). Conclusions of this research is water clover extract affecting increase Lipoprotein Lipase enzymes activity significantly.